Use of Rapid Molecular Polymerase Chain Reaction in Early Detection of Bacteremia in Neonates Prior to Blood Culture Positivity: A Pilot Study - Massa-Buck, Beri; Mendoza, Salome; Keiser, John; Mohamed, Mohamed A. (American Journal of Perinatology, 2022)
Objective There has been national strive to decrease the time needed to identify microorganisms in blood culture samples to reduce antibiotic use. This study evaluated rapid molecular polymerase chain reaction (PCR) use in identifying microorganisms in negative culture bottles from neonates with suspected bacterial blood stream infection at 20 to 24 hours of incubation.Study Design All blood specimens from neonates with suspected blood stream infection were included. Specimens were incubated using a standard blood culturing instrument that would flag positive if bacterial growth was detected. If the specimen was flagged positive at <20 hours, it was tested by PCR and plated for identification as per standard protocol. In our design, if specimen was not flagged at 20 hours of incubation, the bottle was sterilely accessed and a sample was obtained for PCR testing. The bottle would be returned for incubation for 120 hours or until flagged positive.Results A total of 192 blood specimens were included. Four specimens flagged positive at <20 hours and were all found to be positive by PCR. All other samples did not flag positive by 20 hours of incubation and were tested by PCR between 20 and 24 hours. One sample tested positive via PCR at 21.6 hours then flagged positive on the culturing instrument at 23.5 hours. All other specimens were negative by PCR and remained culture negative at 120 hours. The positive and negative predictive value of PCR verified by blood culture were both equal to 1.0.Conclusion Using rapid molecular PCR on blood culture specimens at 20 to 24 hours of incubation provides 100% true negative results possibly allowing providers to discontinue antibiotics at 24 hours.Key Points
Keywords: rapid molecular PCR; neonatal bacteremia; neonatal sepsis; pediatric blood culture